Reconfigurations institutionnelles sur la frontière colombo-vénézuélienne, frontière de tous les trafics - Lina Penagos (Caravelle)
The Colombian-Venezuelan border is a region of significant geostrategic importance. It is partly controlled by non-state armed groups, illustrating how underground economies develop in a region with weak institutions and state structures functioning simultaneously. The growth of organized crime alters the institutional and state architecture of the region. The impact of underground economies in the dynamism of the border, as well as the monopoly of violence outside of State control, open grounds for new research in a gray zone fluctuating between legality and illegality. This situation presents a unique case of study to understand how organized crime affects state institutions and the economic, social, and political life of the Colombian-Venezuelan border region.